“Den guddommeligt skønne natur”: Heideggers Hölderlintolkning og Løgstrups metafysik - Andersen, Svend (Dansk Teologisk Tidsskrift, 2021)
Abstract: The article offers a contribution to the understanding of K.E. Løgstrup’s metaphysics focusing on his reading of Friedrich Hölderlin’s poetry and Martin Heidegger’s interpretation thereof. Heideggerian ontology plays a crucial role in Løgstrup’s theology as a philosophical explication of the pre-understanding of Christian faith. At first, existential ontology was essential in this respect, but later Løgstrup realized the necessity of broadening the view to being in general, which equals the movement towards metaphysics. In this movement, Hölderlin as interpreted by Heidegger is pivotal, an important element being the “poetic openness” Løgstrup introduces in The Ethical Demand. In unpublished manuscripts, Løgstrup claims that poetic openness in Hölderlin has an ontological and metaphysical content, and his reading thereby anticipates central themes in his later metaphysics such as omnipresence, particularity, and the history-nature relation.